Analisa Kekuatan Material Komposit Berbahan Fly Ash dan Serbuk Kaca Bermatrik Resin Epoksi - Bambang Pratowo; Kunarto; Muhammad Irfan Affandy (Universitas Islam Raden Rahmat, Malang, 2023)
Fly ash is produced in large quantities at PLTU Tarahan,South Lampung.Purpose of this research is determine percentage of variations the composite mixture to obtain good composite characteristic properties. Sedangkan komposisi serbuk kaca terdiri dari 3 varian yaitu persentase 10%, 20%, dan 30%, jumlah soal tes sebanyak 21 buah. Komposisi fly ash terdiri dari 3 variasi yaitu persentase 10%, 20% dan 30%. Gaya lentur maksimum untuk komposit yang mengandung 30% fly ash dan 10% serbuk kaca adalah 74,7N and the best impact value lies in 30% fly ash and 10% glass powder of 1.27 J/mm2 highest hardness value at 20% fly ash and 20% glass powder at 81.1 HD.it can be concluded that balance of the composition between fly ash and glass powder has large effect on the hardness value,variations of 30% fly ash and 10% glass powder are optimal conditions for maximum strength in the test bending.